PENGARUH FINANCIAL TECHNOLOGY TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Jurnal Akuntansi, 2023)
This research aims to determine the effect of financial technology on the quality of financial reports with profitability as an intervening variable in banking companies listed on the Indonesia Stock Exchange (BEI). The sample selection technique used was the purposive sampling method. Observation data from 2017-2021. Data analysis uses Partial Least Square (PLS) and Structural Equation Modeling (SEM) methods. The results of this research show that the Automated Teller Machine (ATM) has a positive effect on bank profitability. Mobile banking has a positive effect on bank profitability. Internet Banking has a positive effect on bank profitability. Profitability affects the quality of financial reports, and financial technology has no effect on the quality of financial reports with profitability as an intervening variable. So profitability cannot be used as a link between ATM, mobile banking and internet banking variables on the quality of financial reports. Keywords: Financial Technology, ATM, Mobile Banking, Internet Banking, Profitability, Quality of Financial Reports.